Anti-Museum - Franklin, Adrian (Milton : Routledge, 2019)
Anti-Museum charts the development of the anti-museum as a concept and as it has been realised in practice. Drawing on a range of case studies, including the New Museum and PS1 in New York, Mona in Australia, Art42 in Paris and Donald Judd's Marfa, the book assesses their potential to engage museum publics in new ways. Anti-museums seek to breathe relational and theatricalised vitality into the objects they exhibit, by connecting them to the contexts of their making, to their social life outside the museum, to visitors' lives via their transformative capacities for change, and by being a place of dialogue, exchange and transformation, rather than instruction. Documenting the ways in which they have been created by artists, collectors, and curators, the book also examines the extent to which anti-museums connect with other museums through the exchange of values and resources. Critically, it asks whether, after some 40 years of 'new museology', such institutions are still able to offer something fresh and valuable.
Cover Page; Half Title Page; Series Page; Title Page; Copyright Page; Dedication; Table of Contents; List of figures; Acknowledgements; 1 Introduction: anti-museum -- imagining the unthinkable; 2 Collection de l'Art Brut, Lausanne; 3 Donald Judd's Marfa: state of dialogue; 4 New York, New York: PS1 and the New Museum; 5 Mona (Museum of Old and New Art), Hobart; 6 Art42, Paris; 7 Conclusion: the art of museums beyond convention; References; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Museums